Role of pigeonpea genotypes in influencing the parasitization of Helicoverpa armigera eggs by the parasitoid, Trichogramma chilonis - Hugar, S V; Sharma, H C; Goud, K Basavan; Rahman, S J (Indian Journal of Plant Protection, 2020)
The effect of a diverse array of pigeonpea genotypes on parasitization efficiency of Helicoverpa armigera eggs by the parasitoid, Trichogramma chilonis was studied to identify varieties that are more hospitable to the natural enemies for biological control of this pest. The studies were carried out in the laboratory under no-choice, dualchoice, and multi-choice conditions. Under no-choice conditions, the percentage egg parasitization was high on the pods of ICPB 2042 (27.7) and ICPL 87119 (22.8), while moderate levels of parasitism were recorded on the pods of ICPL 332WR (14.3) and T 21 (12.4) - which also exhibit moderate levels of resistance to H. armigera. High levels of parasitism were also recorded on the flowers of ICPL 332WR (58.6) and LRG 41 (47.2). Parasitism of H. armigera eggs by T. chilonis under dual-choice conditions was greater on the leaves of ICPB 2042 (9.6), LRG 41 (8.5), and ICPL 84060 (8.3) than that on the susceptible check, ICPL 87 (3.4 to 6.7). Under multi-choice conditions, parasitism of H. armigera eggs was greater on the flowers of LRG 41 (18.7), ICPL 84060 (15.3) and ICPB 2042 (13.7) than on ICPL 87 (6.0), and on the pods of ICPB 2042 (15.3), and ICPL 332WR (9.0) as compared to the susceptible check, ICPL 87 (3.0). Lowest egg parasitism was recorded on the wild relative of pigeonpea, Cajanus scarabaeoides (ICPW 125). The genotypes ICPB 2042, ICPL 332 WR, T 21 and LRG 41 that are relatively more hospitable to the egg parasitoid, may be deployed in the farmers’ fields to increase the effectiveness of the egg parasitoid, T. chilonis for reducing the damage by H. armigera.